Netlore Tourism in Pekalongan - Siswo Harsono (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2018)
AbstractNetlore and tourism have a significant relation. The purpose of this research is to investigate the relation between Pekalongan netlore and tourism. This research uses the theory of netlore and folklore tourism. The methods applied in this research are library research and fieldwork. Library research is focused on Pekalongan netlore; and fieldwork is focused on Pekalongan tourism. The findings are that Pekalongan folklore circulated in the internet are used as cultural comunication and tourism promotion. In can be concluded that netlore and tourism have a symbiotic relation in Pekalongan.Keywords: Netlore; folklore; tourism.